The Transaxillary Approach via Prosthetic Conduit for Transcatheter Aortic Valve Replacement With the New-Generation Balloon-Expandable Valves in Patients With Severe Peripheral Artery Disease - Lind, Alexander; Zubarevich, Alina; Ruhparwar, Arjang; Totzeck, Matthias; Jánosi, Rolf Alexander; Rassaf, Tienush; Al-Rashid, Fadi (Frontiers in Cardiovascular Medicine, 2022)
Background: The left subclavian artery (LSA) is an infrequently used alternative access route for patients with severe peripheral artery disease (PAD) in patients who underwent transcatheter aortic valve replacement (TAVR). We report a new endovascular approach for TAVR combining an axillary prosthetic conduit-based access technique with new-generation balloon-expandable TAVR prostheses. Methods and Results: Between January 2020 and December 2020, 251 patients underwent TAVR at the West German Heart and Vascular Center. Of these, 10 patients (3.9%) were deemed to be treated optimally by direct surgical exposure of the left or right axillary artery via a surgically adapted prosthetic conduit. All procedures were performed under general anesthesia. One procedural stroke occurred due to severe calcification of the aortic arch. No specific complications of the subclavian access site (vessel rupture, vertebral, or internal mammary ischemia) were reported. Two minor bleedings from the access site could be treated conservatively. No surgical revision was necessary. Conclusion: The axillary prosthetic conduit-based access technique using new-generation balloon-expandable valves allows safe and successful TAVR in a subgroup of patients with a high risk of procedural complications due to severe peripheral vascular disease. Considering the increasing number of patients referred for TAVR, this approach could represent an alternative for patients with limited access sites.